TANGGUNG JAWAB PELAKU USAHA ATAS PENGGUNAAN OBAT TRADISIONAL YANG MENGANDUNG BAHAN KIMIA OBAT - Ayu Noviyanti, Ni Komang; Wiryawan, I Wayan; Rudy, Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 08, September 2013, 2013)
Businesses is any individual or business entity, whether incorporated or not alegal entity established and domiciled or conducting activities within the jurisdiction ofthe Republic of Indonesia, either alone or jointly conduct business activities throughagreements in various fields of economic. In this paper entitled businessmenresponsibility for the use of traditional medicines that contains drugs chemicals, whichthe issue of how businesses accountable for losses suffered by consumers because theuse of traditional medicines that contain drugs chemicals. Method used is the method ofnormative. Conclusions of this paper businesses responsible for the losses incurred bythe consumer if the consumer has direct knowledge of the drug when consumed containdrugs chemicals.
Keywords: Businesses, Consumer Protection, Traditional Medicine